Turbulent pressure heats gas and suppresses star formation in Galactic bar molecular clouds - Nilipour, Andy; Ott, Juergen; Meier, David S.; Svoboda, Brian; Sormani, Mattia C.; Ginsburg, Adam; Gramze, Savannah R.; Butterfield, Natalie O.; Klessen, Ralf S. (The astrophysical journal, 2024)
The Central Molecular Zone (CMZ) of the Milky Way is fed by gas inflows from the Galactic disk along almost radial trajectories aligned with the major axis of the Galactic bar. However, despite being fundamental to all processes in the nucleus of the Galaxy, these inflows have been studied significantly less than the CMZ itself. We present observations of various molecular lines between 215 and 230 GHz for 20 clouds with ∣ℓ∣ < 10°, which are candidates for clouds in the Galactic bar due to their warm temperatures and broad lines relative to typical Galactic disk clouds, using the Atacama Large Millimeter/submillimeter Array Atacama Compact Array. We measure gas temperatures, shocks, star formation rates, turbulent Mach numbers, and masses for these clouds. Although some clouds may be in the Galactic disk despite their atypical properties, nine clouds are likely associated with regions in the Galactic bar, and in these clouds, turbulent pressure is suppressing star formation. In clouds with no detected star formation, turbulence is the dominant heating mechanism, whereas photoelectric processes heat the star-forming clouds. We find that the ammonia (NH3) and formaldehyde (H2CO) temperatures probe different gas components, and in general, each transition appears to trace different molecular gas phases within the clouds. We also measure the CO-to-H2 X-factor in the bar to be an order of magnitude lower than the typical Galactic value. These observations provide evidence that molecular clouds achieve CMZ-like properties before reaching the CMZ.